A case study on the interior design of a selected mall responsive to the needs of women with children - Cerda, Roxela Veronica R.; Mayo, Adelaida Villaraza (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT This case study aims to identify whether the spatial needs of women pertaining to child care and breastfeeding are addressed by the interior design of a selected mall in Quezon City. Specifically, the study covered the breastfeeding station, day care centers, kiddie cart rentals, vertical transportations and way finding elements found in the selected mall's interior. The subjects of this study were women with children who were chosen through purposive and convenience sampling. Data of this study were obtained from survey questionnaire and key informant interview with experts in the field such as the nurse of the breastfeeding station. The survey was divided into four parts; to provide information on the respondents' knowledge of the laws for women with children, their basic shopping behavior background, and their rating of the variables of the breastfeeding station through the "Likert Scale", and lastly to express their opinions in their own words. The survey results indicated that the shopping mall and its breastfeeding station posed many varying problems, pertaining to insufficient space in the mall's circulation areas and inaccessibility of the public restrooms in the mall. Although the breastfeeding station provided the necessary furniture required for breastfeeding the respondents suggested that piped in music may be added to enhance the space. The study recommends a wider range of respondents that fall under the category of women with children. Furthermore, a comparative study of shopping malls with breastfeeding stations is recommended to be able to further explore the topic at hand.
Thesis (BSID)--University of the Philippines Diliman, 2013.
Keywords: Shopping malls -- Decoration -- Philippines